2019
DOI: 10.1177/2515256419896965
|View full text |Cite
|
Sign up to set email alerts
|

Duo in a Mystical Realm—Nuclear Lipid Droplets and the Inner Nuclear Membrane

Abstract: The lipid droplet (LD) is a cytoplasmic organelle, but it also exists in the nucleus under some conditions or in some cell types. New studies have revealed that nuclear LDs do not occur by haphazard entry of cytoplasmic LDs. Instead, they are generated by specific mechanisms that are increasingly understood. The inner nuclear membrane (INM) plays a critical role in nuclear LD formation in both mammalian hepatocytes and budding yeast, although in significantly different ways. Hepatocyte nuclear LDs derive from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…Lipid droplets consist of neutral lipids, like triacylglycerols and cholesterol esters, coated by a phospholipid monolayer and proteins. They act as lipid reservoirs for energy production and membrane biogenesis, and are now seen as dynamic organelles that can interact with other organelles in a regulated manner [ 18 , 21 ]. Lipid droplets are found in the cytoplasm of many cells, but recent studies have also identified lipid droplets in the nucleus in several cell types, like hepatocytes and hepatocyte-derived cell lines [ 19 , 22 ].…”
Section: Nuclear Envelope and Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid droplets consist of neutral lipids, like triacylglycerols and cholesterol esters, coated by a phospholipid monolayer and proteins. They act as lipid reservoirs for energy production and membrane biogenesis, and are now seen as dynamic organelles that can interact with other organelles in a regulated manner [ 18 , 21 ]. Lipid droplets are found in the cytoplasm of many cells, but recent studies have also identified lipid droplets in the nucleus in several cell types, like hepatocytes and hepatocyte-derived cell lines [ 19 , 22 ].…”
Section: Nuclear Envelope and Lipid Metabolismmentioning
confidence: 99%
“…Recently, several studies have also implicated the nuclear envelope in playing active roles in lipid metabolism. These roles can be played directly through lipid metabolism enzymes situated at the nuclear envelope, by nuclear envelope proteins indirectly affecting transcription of lipidomic genes, or by a combination of these processes [16][17][18][19]. The ER is the main site of lipid synthesis in the cell, with most lipid synthesis enzymes being transmembrane proteins [17].…”
Section: Nuclear Envelope and Lipid Metabolismmentioning
confidence: 99%
“…Consequently, our understanding of LD biology has evolved from that of lipid storage depots to one of dynamic organelles that functionally intersect with many cellular metabolic and signalling activities. This has been further challenged by the discovery and characterization of nuclear lipid droplets (nLD) that share features with their cytosolic counterparts but are unique in terms of biogenesis, their associated proteins and lipids, and ultimately their cellular activities (Sołtysik et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…LDs are often found in the cytoplasm adjacent to the outer nuclear membrane, which is continuous with ER membranes [ 21 ]. However, several recent studies have shown that LDs also occur inside nuclei [ 22 ]. The function(s) of nuclear lipid droplets (nLDs) are not known, but possibilities include providing lipid for the growth of nuclear membranes, storage sites for normal proteins or for unfolded, hydrophobic proteins, and as sites for the detoxification of hydrophobic substances [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The function(s) of nuclear lipid droplets (nLDs) are not known, but possibilities include providing lipid for the growth of nuclear membranes, storage sites for normal proteins or for unfolded, hydrophobic proteins, and as sites for the detoxification of hydrophobic substances [ 23 ]. Few or no nLDs have been observed in some types of cells that contain abundant cLDs, such as adipocytes, or stimulated fibroblasts, but nLDs have been found in multiple types of liver-derived cell lines [ 24 ] and in human patients with fatty-liver disease, or hepatic steatosis [ 22 ]. Obesity-related hepatic steatosis is estimated to affect 20–30% of the population of North America, including very high percentages of patients with morbid obesity or type 2 diabetes (reviewed in [ 20 ]).…”
Section: Introductionmentioning
confidence: 99%